A Hermeneutics of a Barrier-Free Environment for People with Disabilities (Experience of Visual Comment) - A.V, Kukushkina; E.A, Kantaryuk; I.T, Hechiashvili; M.V, Kantaryuk (International Journal of Engineering and Technology, 2018)
At the present time in Russian society there is an attention to the problem of rehabilitation of people with disabilities and their integration into society. In order to create conditions for unhindered access of persons with disabilities to information objects and even to improve their level of living The Government of the Russian Federation approved the state program Â«AccessibilityÂ». One of the objectives of the program is to provide educational, spiritual, information and cultured resources for people with disabilities. Consider the features of perception for the example of people with visual problems. It is known that for the blind, tactile information is necessary, which they can perceive with their fingertips that are the main organs of tactile perception. Also blind people use a so-called white cane to feel the way. The blind and the visually impaired can write and read independently. They do this with their hands, using the relief-point system by Louis Braille. Pay attention to the fact that the sighted person sees the whole object, and then distinguish the details, but a blind person must examine an object on the contour, after that an integral representation is formed. One of the main aspects in a person's life is the spiritual component.Â